2000
DOI: 10.1152/ajpregu.2000.278.4.r905
|View full text |Cite
|
Sign up to set email alerts
|

Systemic bacterial invasion induced by sleep deprivation

Abstract: Profound sleep disruption in humans is generally believed to cause health impairments. Through comparative research, specific physical effects and underlying mechanisms altered by sleep deprivation are being elucidated. Studies of sleep-deprived animals previously have shown a progressive, chronic negative energy balance and gradual deterioration of health, which culminate in fatal bloodstream infection without an infectious focus. The present study investigated the conditions antecedent to advanced morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
165
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(177 citation statements)
references
References 39 publications
6
165
1
1
Order By: Relevance
“…Hence, the suppressing effects of acute experimental sleep loss on immunological memory formation observed in the current study seem to apply also to natural variations in sleep, underscoring the clinical relevance of our findings. Prolonged experimental sleep restriction likewise consistently revealed a negative impact on immune functions (7,49). However, as habitual short sleep and experimental sleep restriction may not always lead to reduced SWS or SWA (50,51), such immunosuppressive effects may stem rather from more pronounced endocrine changes like overall increases in cortisol levels (8).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the suppressing effects of acute experimental sleep loss on immunological memory formation observed in the current study seem to apply also to natural variations in sleep, underscoring the clinical relevance of our findings. Prolonged experimental sleep restriction likewise consistently revealed a negative impact on immune functions (7,49). However, as habitual short sleep and experimental sleep restriction may not always lead to reduced SWS or SWA (50,51), such immunosuppressive effects may stem rather from more pronounced endocrine changes like overall increases in cortisol levels (8).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the human studies were performed mainly on depressive patients, and it is doubtful whether these can be regarded as a representative group of the whole population. In animal experiments, after 72 hours of sleep loss, the level of the corticotropin-releasing hormone (CRH) changed the absence of the nocturnal maximal GH release in the sleep-deprived animals [72,73], or to a tendency for such animals to become infected with their own migrating bacterial flora [74]. These conjectures are in contradiction with the findings indicating that REM loss does not disrupt the wound healing process [75].…”
Section: Dermal Effectsmentioning
confidence: 92%
“…However, even the authors themselves have found this outcome surprising. The sleep-deprived animals develop infections of the lymph glands and other tissues, which are induced by their own intestinal bacterial flora [74]. This can take place only in the state of immunological suppression.…”
Section: Dermal Effectsmentioning
confidence: 99%
“…83). Already well established is the fact that acutely sustained total sleep deprivation in laboratory rats results in a progressive negative energy balance (2, 20, 28), suppression of major anabolic hormones (21, 24), and immune-related abnormalities (18,19,26,27) that turn lethal after an average of 16 to 21 days (20,53,55,62). However, rats that obtain nearly half-normal sleep amounts during the same time period do not develop severe pathology and do not die (20,53,55,62).…”
mentioning
confidence: 99%